Between a Butterfly and a Cathedral: The Question of Art in Brideshead Revisited by Evelyn Waugh - Slawomir Koziol (Miscelánea: A Journal of English and American Studies, 2015)
The article explores Evelyn Waugh’s views on art, especially his criticism of modernism, expressed in his novel Brideshead Revisited. Drawing on the works of aesthetic theory alluded to or directly mentioned in the novel, as well as on the existing literary criticism on the work, the article examines Waugh’s idea of the function and value of art through a close reading of key fragments of the novel dealing with the question of art. The article argues that Waugh’s criticism of the modernist aesthetics finds its closest ally and its best theoretical elucidation in one of the less known —and most probably unknown to Waugh himself— texts of Roger Fry, who is generally considered to be an icon for practitioners and theorists of modernist art Britain and who plays such a role in Waugh’s novel.